Exploring social media usage as a communication channel among independent food retailer SMEs in South Africa - José dos Santos; Rodney Duffett (Small Business International Review)
Social media has facilitated interaction between businesses and consumers, and consequently, has seen rapid growth as a communication channel by a number of smaller retailers in South Africa. Hence, the primary research objective of this study is to explore social media usage as a marketing communication strategy by independent food retailer small to medium enterprises (SMEs). The study used a qualitative data collection strategy and in-depth interviews were conducted among eleven independent food retailer SMEs in South Africa. The study revealed that the level of social media activity by the respondent retailers was influenced by enabling factors such as cost effectiveness, accessibility, reach and relationship building, whereas perceived risk and resources such as time, knowledge and human resources were inhibiting factors. The research contributes to the available literature exploring social media usage as customer contact points for promotional purposes, as well as provides insight for further studies on the use of social media conduits by independent food retailer SMEs or similar businesses in a developing country.